Flexible molecular crystals for optoelectronic applications - Wei, Chuanxin (2024)
The cornerstones of the advancement of flexible optoelectronics are the design, preparation, and utilization of novel materials with favorable mechanical and advanced optoelectronic properties. Molecular crystalline materials have emerged as a class of underexplored yet promising materials due to the reduced grain boundaries and defects anticipated to provide enhanced photoelectric characteristics. An inherent drawback that has precluded wider implementation of molecular crystals thus far, however, has been their brittleness, which renders them incapable of ensuring mechanical compliance required for even simple elastic or plastic deformation of the device. It is perplexing that despite a plethora of reports that have in the meantime become available underpinning the flexibility of molecular crystals, the “discovery” of elastically or plastically deformable crystals remains limited to cases of serendipitous and laborious trial-and-error approaches, a situation that calls for a systematic and thorough assessment of these properties and their correlation with the structure. This review provides a comprehensive and concise overview of the current understanding of the origins of crystal flexibility, the working mechanisms of deformations such as plastic and elastic bending behaviors, and insights into the examples of flexible molecular crystals, specifically concerning photoelectronic changes that occur in deformed crystals. We hope this summary will provide a reference for future experimental and computational efforts with flexible molecular crystals aimed towards improving their mechanical behavior and optoelectronic properties, ultimately intending to advance the flexible optoelectronic technology.